The Evolution of Primary Health Care Teams and Integrated Health Services Delivery in Four Canadian Provinces - Nelly Oelke; Ashmita Rai (McMaster University Library Press, 2023)
Improving integrated health services for patients with two or more chronic illnesses is a priority in Canada as our health systems grapple with their complex needs and the services they require (Kirst et al. 2017; Suter et al. 2014). Team-based primary health care (PHC) models have been implemented in diverse ways to improve patient experience and to bet- ter coordinate integrated care to improve population health and reduce the cost of health care (Kirst et al. 2017; Buljac-Samardzic et al. 2010). The structure and composition of interprofessional primary health care (IPHC) models vary across provinces; however, their common goal is to address the four elements of the Quadruple Aim (population health, patient experience, provider experience, and reducing costs) (Bodenheimer and Sinsky 2014). Although research exists on interprofessional teams and health service integration, understanding the effectiveness of the development and implementation of team-based models for patients with two or more chronic illnesses has been challenging. Policymakers, decision-makers, providers, and patient groups have little evidence on what policies and structures facilitate, incentivize, or prevent integrated service delivery, especially for patients with complex needs. This knowledge gap has had an impact on the reform of service integration for patients with complex needs through IPHC teams. A policy analysis was conducted in four Canadian provinces to examine the policies and structures that scaffold such reform, identifying barriers and facilitators to the implementation of PHC teams and integrated health services. This study was carried out in British Columbia (BC), Alberta (AB), Ontario (ON), and Québec (QC) to understand different models implemented in these provinces and to ensure representation of east, west, and central Canada.